CYBERCRIME AND CYBERTERRORISM (Sciental Journal of Education Humanities and Social Sciences, 2025)
Cyberspace is often presented in the form of a hyperset, which is associated with the idea of decentralized open access network structures of manufacturing, commerce, services, and other organizations. Openness wins the competition. Cyberbullying is sometimes seen as a verbal structure with hypertext, internal photographs, and video material.